2020
DOI: 10.1080/09638288.2020.1829106
|View full text |Cite
|
Sign up to set email alerts
|

Dexterity, activity performance, disability, quality of life, and independence in upper limb Veteran prosthesis users: a normative study

Abstract: Purpose: To present population data on standardized measures of dexterity, activity performance, disability, health-related quality of life (HRQoL) and community integration for persons with upper limb amputation (ULA), compare outcomes to normative values, and examine differences by prosthesis type and laterality (unilateral vs. bilateral amputation). Materials and methods: Multi-site, cross-sectional design, with in-person evaluations, functional performance, and self-report measures. Descriptive and compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Finally, to examine whether the PROMIS UE versions differed for subgroups as expected based on clinical observation and previous research, 25 we compared scores of the six various configurations of the PROMIS measure for prosthesis users and nonusers and for persons of varying amputation level. Because of potential confounding of amputation level and prosthesis use (persons with more proximal amputation are less likely to be prosthesis users), we also stratified the data by prosthesis use and compared scores within amputation level.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to examine whether the PROMIS UE versions differed for subgroups as expected based on clinical observation and previous research, 25 we compared scores of the six various configurations of the PROMIS measure for prosthesis users and nonusers and for persons of varying amputation level. Because of potential confounding of amputation level and prosthesis use (persons with more proximal amputation are less likely to be prosthesis users), we also stratified the data by prosthesis use and compared scores within amputation level.…”
Section: Discussionmentioning
confidence: 99%
“…The DIF analyses suggested that bilateral amputees found tasks requiring fine force regulation with the prosthesis easier than unilateral amputees, but certain dexterous bilateral activities, such as tying a knot, more difficult than unilateral amputees. Neither of these results are surprising, given that bilateral amputees cannot rely on their intact limb for fine force regulation and thus develop more dexterity on their dominant prosthetic side [27]. Further, bilateral amputees cannot use an intact limb during bilateral activities, making these activities more difficult.…”
Section: Difficulty Of Items Within Each Scalementioning
confidence: 97%
“…Participants in this analytic subsample were a subset of the sample recruited for a more comprehensive parent study described elsewhere. 2 These subjects were a convenience sample of service members, veterans, and civilians who had unilateral major ULA or limb deficiency at the above-elbow (AE) or below-elbow (BE) level. The AE levels included elbow disarticulation (ED) and transhumeral (TH) levels.…”
Section: Samplementioning
confidence: 99%